2010
DOI: 10.1177/201010581001900103
|View full text |Cite
|
Sign up to set email alerts
|

Different cagA and vacA Polymorphisms are Found in the Chinese versus the Malay and Indian Populations: An Analysis of Helicobacter Pylori Virulence Genes in Singapore

Abstract: Aim:Helicobacter pylori causes peptic ulcer disease and gastric cancer. Western studies suggest that polymorphisms in the virulence factors caga and vaca may determine the ability of bacteria to cause gastroduodenal diseases. Differences in the caga EPIYA motifs and polymorphisms of the signal (s), middle (m) and intermediate (i) regions of vaca are thought to be important. The aim of this study was to compare the polymorphisms of caga and vaca of H. pylori isolated from the Chinese, Malay and Indian populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
(33 reference statements)
1
4
0
Order By: Relevance
“…looking at CagA EPIYA motifs strains from our center and another center from Singapore with the same racial mix, it was found that the majority of strains derived from Chinese patients with functional dyspepsia and GCA harbored the more virulent EPIYA ABD motif, whereas the Malay and Indian isolates were predominately that of the ABC motif . Similar results were noted form other studies from Malaysia and Singapore where Chinese strains were again predominantly ABD motif compared with Malay and Indian strains, which were of the ABC or ABCC motif …”
Section: Gastric Cancer Paradox—“the Indian Enigma”supporting
confidence: 86%
See 3 more Smart Citations
“…looking at CagA EPIYA motifs strains from our center and another center from Singapore with the same racial mix, it was found that the majority of strains derived from Chinese patients with functional dyspepsia and GCA harbored the more virulent EPIYA ABD motif, whereas the Malay and Indian isolates were predominately that of the ABC motif . Similar results were noted form other studies from Malaysia and Singapore where Chinese strains were again predominantly ABD motif compared with Malay and Indian strains, which were of the ABC or ABCC motif …”
Section: Gastric Cancer Paradox—“the Indian Enigma”supporting
confidence: 86%
“…Lui et al showed that Malay and Indian isolates showed an s1/m1/i1 allelic pattern while the Chinese showed a mixture of s1/m1/i1 and an s1/m2/i1 allelic combination. 29 In another study, Alfizah et al again showed a similar gene combination of s1/m1 and s1/m2 in Chinese while the Malays and Indians showed a predominant allelic type of s1/m1. 30 Tan et al sub typed the s1 allele and showed that the s1a gene was predominant in Malays and Indians and the s1c gene in Chinese.…”
Section: Gastric Cancer Paradox-"the Indian Enigma"mentioning
confidence: 91%
See 2 more Smart Citations
“…Bagheri et al. revealed the high abundance of vacA i1 allele in Iranian patients [ [24] , [25] , [26] ].…”
mentioning
confidence: 99%